Crystal structures of bovine milk xanthine dehydrogenase and xanthine oxidase: Structure-based mechanism of conversion - Enroth, Cristofer (The National Academy of Sciences, 2000)
Mammalian xanthine oxidoreductases, which catalyze the last two steps in the formation of urate, are synthesized as the dehydrogenase form xanthine dehydrogenase (XDH) but can be readily converted to the oxidase form xanthine oxidase (XO) by oxidation of sulfhydryl residues or by proteolysis. Here, we present the crystal structure of the dimeric (M(r), 290,000) bovine milk XDH at 2.1-Å resolution and XO at 2.5-Å resolution and describe the major changes that occur on the proteolytic transformation of XDH to the XO form. Each molecule is composed of an N-terminal 20-kDa domain containing two iron sulfur centers, a central 40-kDa flavin adenine dinucleotide domain, and a C-terminal 85-kDa molybdopterin-binding domain with the four redox centers aligned in an almost linear fashion. Cleavage of surface-exposed loops of XDH causes major structural rearrangement of another loop close to the flavin ring (Gln 423—Lys 433). This movement partially blocks access of the NAD substrate to the flavin adenine dinucleotide cofactor and changes the electrostatic environment of the active site, reflecting the switch of substrate specificity observed for the two forms of this enzyme.